THE EFFECT OF INTELLECTUAL PROPERTY ON THE PERFORMANCE OF NON-FINANCIAL COMPANIES IN INDONESIA WITH A MARKET VALUE APPROACH - Gracia S. Ugut; Glenn Natanael (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The global economy is rising swiftly and transforming into a modern knowledge-based economy as it enters industrial era 4.0. These advancements have caused many businesses to rely not only on material assets, but also on intangible assets. The present economic era also makes competition between firms more intense, necessitating that companies always provide the best performance in creating value through their distinctiveness and competitive edge. Based on how the market values a company, its performance can be measured. This study attempts to determine the impact of intellectual capital on corporate performance based on market value. Utilizing the intellectual capital index, this study measures intellectual capital. The data in this study used a population of all non-financial firms listed on the Jakarta Stock Exchange as many as 579 firms with an observation period of 2016 - 2020, which were then selected as research samples of 199 samples. The hypothesis in this study was analyzed using panel data regression. The results of this study indicate that intellectual capital has a positive and significant effect on company performance based on the market value approach. This implies that knowledge regarding how companies manage their intellectual capital can affect market prices. This research enables nonfinancial organizations to pay greater attention to intellectual capital, which is an immaterial asset that may be further developed to create value and improve performance of an organization.